Challenges of Guidance and Counselling Services as Expressed by Counsellors in Armed Forces Schools Nigeria - Fakokunde, Mosadoluwa O.; Oyebanji, Temitope O.; Akinnusi, Ayorinde E. (Education and Development Research, 2026)
The study was conducted to determine the challenges of guidance and counselling practices as expressed by counsellors in armed forces schools in Nigeria. The research design adopted for the study is the descriptive survey, it was done by employing the multistage sampling procedure to draw two hundred samples across all armed forces schools in Nigeria. Findings from the study revealed that all hypotheses tested were accepted as no significant difference exists among the variables. Based on the findings, it was recommended that counsellors in armed forces schools require further training so as to enhance their performance, it was also recommended that counsellors in armed forces schools should be relieved of other duties so as to enhance their performance.